SOLID-LIQUID EXTRACTION OF JOJOBA OIL OBTAINED BY THE PROCESS AND THE PROCESS VARIABLES OIL EFFECTS ON YIELD - Altin, Zehra Gulten; Keyf, Seyfullah; Corbacioglu, Burcu Didem; Beyribey, Berceste (YILDIZ TECHNICAL UNIV, 2013)
In this study, hexane was used as solvent to extract Jojoba oil in a batch leaching process. The effects of temperature, mixing speed, particle size and solvent-to-seed ratio on Jojoba oil extraction were investigated. The best yield of oil was obtained when the parameters investigated were at the boiling point temperature of the solvent, a particle size of 0,48 mm, a mixing speed of 1000 rpm, and a solvent-to-seed ratio of 15 ml/g. The maximum amount exracted was 55 wt-% under the above-mentioned operating conditions. The amount extracted at a higher particle size (1,5 mm) was around 44 wt-%. An empirical model was obtained based on the experimental data, in order to predict the extraction yield under the operating conditions. The derived model is in good agreement with the experimental data, with a maximum deviation of 8%.
Keywords: Jojoba; jojoba oil; solid-liquid extraction; solid-liquid extraction parameters; Engineering